A série "A Mediadora" e as jovens leitoras - Chaves, Rovana (2010)
This research has as object of study the series "The Mediator , by Meg Cabot. In this investigation, related to the line of research Reading and reader formation , are observed the reading experiences of twenty young adults with ages between thirteen and twenty seven years old, which make part of a reading community, also named The Mediator hosted in Orkut. The data collected by a questionnaire applied to the group by electronic mail are analyzed based on the studies of Reception Aesthetics and the Theory of the Effect,performed,respectively by Hans Robert Jauss e Wolfgang Iser.The overall objective of this study is to understand the experiences and preferences that these readers have in common and results in the choice of the series in focus. The specifics objectives are:Verifying if all the participants had the same kind of reading formation and which were the factors and mediators involved in this process; Observing the reasons that lead them to choose this collection, related with their real experience and literally experience; Showing not only the way thatthe text, the reading and the author interact, as the way the young readers receipt the series, highlighting their expectations related to the book, and, finally, analyzing the way that occurs the reading socialization between the researches. The writing of this study, by qualitative, interpretive and bibliographic research, is justified by the fewer studies related with the reading reception of the young female audience